Influence of Service Quality, Customer Satisfaction and Commitment to Customer Loyalty among Banking Consumer - Nurcahaya, Nurcahaya; Junaidi, Junaidi; Anwar, Suhardi Mappe (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2022)
This study aims to determine the effect of service quality, customer satisfaction, and commitment on customer loyalty at Bank BRI. This research method uses quantitative methods with a population of customers who save at the BRI Persero Palopo branch of the bank. The sample used is 320 respondents, and the data is measured using a numerical scale (numbers). After the analysis, the results obtained showed that service quality has a positive effect on commitment, customer satisfaction has a positive effect on commitment, and commitment has a positive effect on loyalty.